Plasmonic petal-shaped beam for microscopic phase-sensitive SPR biosensor with ultrahigh sensitivity - Wang, Rong (EEE) (2014)
Differential phase measurement between radially polarized (RP) and azimuthally polarized (AP) beams is an important technique in microscopic surface plasmon resonance (SPR) biosensors as reported in our earlier works [Opt. Lett. 37, 2091 (2012); Appl. Phys. Lett. 102, 011114 (2013)]. However, such a technique suffers complex beam splitting, detection, and data processing procedures for RP and AP beams which may lower the accuracy of phase measurement. In this Letter, a novel plasmonic petal-shaped vector beam is proposed instead of RP and AP beams, greatly simplifying the sensor system and enabling single measurement in differential interferometry. Moreover, an improved ultrahigh sensitivity on the order of 10−7 refractive index units (RIUs) is experimentally verified in the proposed system.